2005
DOI: 10.1016/j.eeh.2004.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging financial markets and early US growth

Abstract: Studies of early U.S. growth traditionally have emphasized real-sector explanations for an acceleration that by many accounts became detectable between 1815 and 1840. Interestingly, the establishment of the nation's basic financial structure predated by three decades the canals, railroads, and widespread use of water and steam-powered machinery that are thought to have triggered modernization. We argue that this innovative and expanding financial system, by providing debt and equity financing to businesses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(68 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…The early empirical work of King and Levine (1993a,b) suggested that financial depth is an important part of what explains variations in growth across countries. The robustness of that connection has been supported by subsequent studies such as Demirgüç-Kunt and Maksimovic (1998), Levine et al (2000) and Rousseau and Sylla (2005). 1 A number of other results have suggested that the empirical evidence is not consistently positive, however.…”
Section: Introductionsupporting
confidence: 52%
“…The early empirical work of King and Levine (1993a,b) suggested that financial depth is an important part of what explains variations in growth across countries. The robustness of that connection has been supported by subsequent studies such as Demirgüç-Kunt and Maksimovic (1998), Levine et al (2000) and Rousseau and Sylla (2005). 1 A number of other results have suggested that the empirical evidence is not consistently positive, however.…”
Section: Introductionsupporting
confidence: 52%
“…59-93). The establishment of the Bank of England in 1694, and the introduction of a money market, checks and an active stock exchange in the late 17 th century have been described as a financial revolution (Deane, 1969, Ch 11;Rousseau and Sylla, 2005). Furthermore, notes issued by the Bank of England and by private banks in the 17 th and 18 th centuries, were essential for the development of a modern financial system (Deane, 1969, Ch 11).…”
Section: Empirical Models Of Economic Growthmentioning
confidence: 99%
“…Furthermore, notes issued by the Bank of England and by private banks in the 17 th and 18 th centuries, were essential for the development of a modern financial system (Deane, 1969, Ch 11). The ratio of broad money to GDP is used here as a proxy for financial development, which is standard in the literature on financial development and growth (see, e.g., Rousseau and Sylla, 2005;Ang and McKibbin, 2007;Ang, 2010).…”
Section: Empirical Models Of Economic Growthmentioning
confidence: 99%
“…al. (2001); Rousseau (2003); Rousseau and Sylla (2005)) as well as in emerging economies (Khan and Senhadji (2003); Eita and Jordan (2007) ;Akinlo and Egbetunde (2010) ;Acaravci et. al.…”
Section: Introductionmentioning
confidence: 99%